A Health Care Project Management Office's Strategies for Continual Change and Continuous Improvement. Issue 1 (January 2018) - Lavoie-Tremblay, Mélanie; Aubry, Monique; Richer, Marie-Claire; CYR, Guylaine
Abstract : Health care organizations need project and change management support in order to achieve successful transformations. A project management office (PMO) helps support the organizations through their transformations along with increasing their capabilities in project and change management. The aim of the present study was to extend understanding of the continuous improvement mechanisms used by PMOs and to describe PMO's strategies for continual change and continuous improvement in the context of major transformation in health care. This study is a descriptive case study design with interviews conducted from October to December 2015 with PMO's members (3 managers and 1 director) and 3 clients working with the PMO after a major redevelopment project ended (transition to the new facility). Participants suggested a number of elements including carefully selecting the members of the PMO, having a clear mandate for the PMO, having a method and a discipline at the same time as allowing openness and flexibility, clearly prioritizing projects, optimizing collaboration, planning for everything the PMO will need, not overlooking organizational culture, and retaining the existing support model. This study presents a number of factors ensuring the sustainability of changes.